PSMA-targeted radionuclide therapy of metastatic castration-resistant prostate cancer with 177Lu-labeled PSMA-617 - Kratochwil, Clemens; Giesel, Frederik L.; Stefanova, Melsa; Afshar-Oromieh, Ali; Mier, Walter; Haberkorn, Uwe (Journal of nuclear medicine, 2016)
Prostate-specific membrane antigen (PSMA) is an excellent target for radionuclide therapy of metastasized castration-resistant prostate cancer (mCRPC). Besides high affinity and long tumor retention, the DOTA-conjugated ligand PSMA-617 has low kidney uptake, making it an excellent choice for therapeutic application. We retrospectively report our experience with 177Lu-PSMA-617-targeted radionuclide therapy in a case series of mCRPC patients resistant to other treatments. Methods: Patients with PSMA-positive tumor phenotypes were selected by molecular imaging. Thirty patients received 1-3 cycles of 177Lu-PSMA-617. During therapy, pharmacokinetics and radiation dosimetry were evaluated. Blood cell count was checked every 2 wk after the first and every 4 wk after succeeding cycles. Prostate-specific antigen (PSA) was determined every 4 wk. Radiologic restaging was performed after 3 cycles. Results: Twenty-one of 30 patients had a PSA response; in 13 of 30 the PSA decreased more than 50%. After 3 cycles, 8 of 11 patients achieved a sustained PSA response (>50%) for over 24 wk, which also correlated with radiologic response (decreased lesion number and size). Normally, acute hematotoxicity was mild. Diffuse bone marrow involvement was a risk factor for higher grade myelosuppression but could be identified by PSMA imaging in advance. Xerostomia, nausea, and fatigue occurred sporadically (<10%). Clearance of non-tumor-bound tracer was predominantly renal and widely completed by 48 h. Safety dosimetry revealed kidney doses of approximately 0.75 Gy/GBq, red marrow doses of 0.03 Gy/GBq, and salivary gland doses of 1.4 Gy/GBq, irrespective of tumor burden and consistent on subsequent cycles. Mean tumor-absorbed dose ranged from 6 to 22 Gy/GBq during cycle 1. Conclusion: 177Lu-PSMA-617 is a promising new option for therapy of mCRPC and deserves more attention in larger prospective trials.
Im Titel ist "177" in 177Lu-labeled hochgestellt
Gesehen am 26.03.2018